Retrospective Analysis of Use of Empiric Anit Tuberculosis Treatment in Smear Negative Pulmonary Tuberculosis Patients in Central Sri Lanka - Madegedara, D; Kulathunga, KMCN; Nakandala, SC (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Objective: To critically analyze the outcome of sputum negative pulmonary TB patients who were managed in the Respiratory unit, Kandy Sri Lanka. Setting: Respiratory Unit, Teaching hospital, Kandy. Method: The subjects were between age 12 years or older and visited chest clinic Kandy, between January -December 2008 with a suspicion of pulmonary TB. 84 patients were reviewed with admission note, microbiology results and chest radiography. The characteristics of patients such as age, sex, clinical features, laboratory and radiographic findings were analyzed. Results: The diagnosis of definite or probable smear negative pulmonary TB was made on treatment outcome at one month with ATT medication. At this endpoint, 67 (79.76%) had clinical and radiological improvement, 7(8.33%) had clinical improvement and 3 (3.57%) had radiological improvement. Mantoux test was positive in 46(78%) of definite cases and 6(85.7%) in probable cases. Mycobacterial culture was positive in 5 patients. 7 (8.3%) cases were diagnosed as ‘non-TB’ based on absence of clinical / radiological improvement or discovery of another cause at or before this study end point. In non TB group 3 had carcinoma, 2 had pneumoconiosis, 1 had bronchiectasis while in 1, cause was indeterminate. Mantoux became positive in 6 (83.3%) in non Tuberculosis group. There was no association between positive Mantoux and presence of active pulmonary TB. Conclusion: Our findings suggest that empirical anti TB treatment is an acceptable practice if clinical suspicion of tuberculosis is high and patients show supportive radiological evidence of active TB. Keywords: Smear negative pulmonary tuberculosis; empirical anti tubercular treatment DOI: 10.3126/saarctb.v7i2.4400 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 15-18